(untitled) (Tanzania Medical Journal, 2025)
Background Peripartum cardiomyopathy (PPCM) is a rare heart disease which affects previously health women toward the end of pregnancy or within five months following delivery. The incidence of PPCM shows wide regional variations and has been rising, probably due to increased risk factors and the incidence in Tanzania is unclear. The aim of this study was to determine the temporal trends in incidence and maternal outcomes among PPCM patients attended at the largest tertiary hospital in Tanzania -Muhimbili National Hospital. Methods A descriptive retrospective case review study was done at Muhimbili National Hospital (MNH). A five-year review (July 2013-June 2018) of 129 case notes from the patients with PPCM was conducted. Trends of incidence of PPCM and maternal outcomes (maternal death, pulmonary edema, thromboembolism and stroke, cardiogenic shock and length of hospital stay) following PPCM were analysed. The Pearson’s coefficient test was used to determine the temporal trends in incidence of Peripartum cardiomyopathy over the study period. P-value of less than 0.05 was considered statistically significant. Result The overall incidence of Peripartum cardiomyopathy for five years was 3.0 per 1000 live births (1 in 333). There was observed increase in incidence rate from 1.4 in the first year to 4.8 in the fifth year of study which was statistically significant with P trend <0.0001. The most common complications observed in women with Peripartum cardiomyopathy in the overall cohort was pulmonary edema 31%, maternal death 7.8%, thromboembolism/stroke 4.7 % and cardiogenic shock 4.7 %. The average hospital stay was 9 days. Conclusion There was an overall increase in the incidence of Postpartum cardiomyopathy at Muhimbili National Hospital in the five-year period. The most common complications were pulmonary edema and maternal death.